2019
DOI: 10.7150/ijbs.29741
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Export and Ubiquitin-Proteasome-Dependent Degradation of PPARγ Induced By Angiotensin II

Abstract: Evidence has documented local angiotensin II (Ang II) as a pro-oxidant and pro-inflammatory molecule contributes to progressive deterioration of organ function in diseases. Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-activated transcription factor, plays crucial roles in protection against oxidative stress and inflammation. Ang II stimulation decreases PPARγ protein in multiple types of cells, while the regulatory role of Ang II on PPARγ is not clear. Here we show that Ang II down-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…RBCK1 interacts with different substrates in order to exert its effects. Studies have reported that the ubiquitin-proteasome-mediated degradation of PPARγ is the critical mechanism by which PPARγ levels are regulated in cells [33]. Similarly, our results suggest, for the rst time, that RBCK1 destroyed the PPARγ/PGC1α complex by promoting the ubiquitination and degradation of PPARγ.…”
Section: Discussionsupporting
confidence: 76%
“…RBCK1 interacts with different substrates in order to exert its effects. Studies have reported that the ubiquitin-proteasome-mediated degradation of PPARγ is the critical mechanism by which PPARγ levels are regulated in cells [33]. Similarly, our results suggest, for the rst time, that RBCK1 destroyed the PPARγ/PGC1α complex by promoting the ubiquitination and degradation of PPARγ.…”
Section: Discussionsupporting
confidence: 76%
“…We recently reported that the high levels of PSMC family members, including PSMC1, PSMC3, PSMC4, PSMC5, and PSMC6, were positively correlated with the poor survival rates of BRCA patients [ 45 ]. Peroxisome proliferator-activated receptor γ (PPARγ) is also associated with ubiquitin–proteasome-dependent degradation and response to the angiotensin II (Ang II) system [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. However, whether PSMA family genes are also involved in BRCA development still needs to be more thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we found microglial Pdcd4 deletion abolished LPSinduced microglia activation via up-regulating PPARγ expression and nucleus translocation. We thought there is a causal link between PPARγ up-regulation and nucleus transportation, for rapidly ubiquitinproteasome mediated degradation of cytosol distributed PPARγ [25]. E3 RING ubiquitin ligases have reported, such as NEDD4-1, TRIM25, FBXO9, MKRN1, CUL4B, and FBXO4, regulate PPARγ protein levels which contribute to adipogenesis [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%